Cesarean section by maternal request - CÂMARA,RAPHAEL (2016)
ABSTRACT Cesarean section by maternal request is the one performed on a pregnant woman without medical indication and without contraindication to vaginal delivery. There is great controversy over requested cesarean section. Potential risks include complications in subsequent pregnancies, such as uterine rupture, placenta previa and accreta. Potential benefits of requested cesareans include a lower risk of postpartum hemorrhage in the first cesarean and fewer surgical complications compared with vaginal delivery. Cesarean section by request should never be performed before 39 weeks.